Development and challenges in the implementation of sustainable development goals (SDGs) in Indonesia: A systematic literature review - Novita, Asti Amelia; Ngindana, Rispa; Putra, Endry; Virgiyansha, Danica; Nalendra (Jurnal Inovasi Ilmu Sosial dan Politik (JISoP), 2023)
Efforts towards achieving the Sustainable Development Goals (SDGs) in Indonesia have been underway for approximately eight years. Throughout this period, these efforts have experienced ups and downs. Through the systematic literature review method, this research aims to analyze the progress and challenges in the implementation of SDGs in Indonesia, focusing on four aspects: policy alignment, stakeholder engagement, resources and finances, as well as monitoring and evaluation. The systematic literature review process involves the comprehensive identification, selection, quality assessment, synthesis, and interpretation of relevant literature to address research questions. The research results indicate that there are still several challenges to be addressed in the pursuit of SDGs, including regional inequality, lack of coordination among stakeholders, and issues related to transparency and public accountability. In achieving sustainable development goals in Indonesia, collaboration among stakeholders is necessary to address these challenges.